Analysis of total harmonic distortion in single-phase single-stage grid-connected photovoltaic system - Nurhazwani Anang; Wan Mariam Wan Muda (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
This study presents the power quality issue mainly focus the effect of total harmonic distortion (THD) on a grid-connected PV system. Firstly, a grid-connected PV system with a single-phase single-stage has been developed to monitor the output values of voltage and current and also its harmonic distortion behaviours. Maximum power point tracking (MPPT) was implemented since it is proven as the first step for THD reduction because MPPT will extract maximum output power, voltage, and current of the PV system without fluctuation which leads to a low THD level. Furthermore, the employment of a good filter also reduces the THD level in a PV system. Thus, this study will focus on the THD analysis to resolve the power quality problems in the grid-connected PV system. The result shows that the THD value for current, ITHD analysis is more significant than the THD value for voltage, VTHD analysis in the case of grid-connected PV systems operating under different solar irradiances. In a conclusion, the increase in solar irradiance will increase the rated values of generated power and current thus, increasing the performance of THD values.